Mitochondrial Superoxide Increases Age-Associated Susceptibility of Human Dermal Fibroblasts to Radiation and Chemotherapy - Mapuskar, Kranti A; Flippo, Kyle H; Schoenfeld, Joshua D; Riley, Dennis P; Strack, Stefan; Hejleh, Taher Abu; Furqan, Muhammad; Monga, Varun; Domann, Frederick E; Buatti, John M; Goswami, Prabhat C; Spitz, Douglas R; et al. (Cancer research (Chicago, Ill.), 2017)
Elderly cancer patients treated with ionizing radiation (IR) or chemotherapy experience more frequent and greater normal tissue toxicity relative to younger patients. The current study demonstrates that exponentially growing fibroblasts from elderly (old) male donor subjects (70, 72, and 78 years) are significantly more sensitive to clonogenic killing mediated by platinum-based chemotherapy and IR (∼70%-80% killing) relative to young fibroblasts (5 months and 1 year; ∼10%-20% killing) and adult fibroblasts (20 years old; ∼10%-30% killing). Old fibroblasts also displayed significantly increased (2-4-fold) steady-state levels of O , O consumption, and mitochondrial membrane potential as well as significantly decreased (40%-50%) electron transport chain (ETC) complex I, II, IV, V, and aconitase (70%) activities, decreased ATP levels, and significantly altered mitochondrial structure. Following adenoviral-mediated overexpression of SOD2 activity (5-7-fold), mitochondrial ETC activity and aconitase activity were restored, demonstrating a role for mitochondrial O in these effects. Old fibroblasts also demonstrated elevated levels of endogenous DNA damage that were increased following treatment with IR and chemotherapy. Most importantly, treatment with the small-molecule, superoxide dismutase mimetic (GC4419; 0.25 μmol/L) significantly mitigated the increased sensitivity of old fibroblasts to IR and chemotherapy and partially restored mitochondrial function without affecting IR or chemotherapy-induced cancer cell killing. These results support the hypothesis that age-associated increased O and resulting DNA damage mediate the increased susceptibility of old fibroblasts to IR and chemotherapy that can be mitigated by GC4419. .